LIVELIHOOD MASYARAKAT KAMPUNG PELANGI, GUNUNG BRINTIK, KOTA SEMARANG MELALUI PENDEKATAN SUSTAINABLE URBAN LIVELIHOOD (SUL) - Tia Adelia Suryani; Haryo Winarso (Diponegoro University, 2019)
The rapid growth of the population of Semarang City and the limited land for settlements resulted in the emergence of illegal slums. One of the government's efforts to revitalize the slum area by coloring Gunung Brintik village area which became known as Kampung Pelangi. Some slum revitalization programs in other countries have not succeeded in increasing residents’ livelihood. The purpose of this study was to examine the success of the government in improving the livelihood of Kampung Pelangi in Semarang City, through the Sustainable Urban Livelihood (SUL) approach with quantitative descriptive methods and scoring analysis techniques. The study was conducted at two different times; before the implementation of the Semarang City Government program (in 2016) and after the implementation (in 2018). As a control, Kampung Pandean was chosen because it had similar conditions but did not get any program from the government. The results showed that there was a change in the livelihood of the population in Kampung Pelangi include the quality of human capital, natural capital, social capital, and physical capital, while the condition of Kampung Pandean does not show any changes during 2016-2018. This change is not due to coloring but due to improvements in physical conditions.